How does board diversity affect the financial performance of commercial banks in indonesia? An inquiry - Arquisola, Maria Jacinta; Shella, Kezia; Hutabarat, Erny (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
This study analyzes board diversity and its effect on financial performance, as measured by age, gender, and nationality of board members using a sample of nine (9) commercial banks in Cikarang, West Java, Indonesia. The study uses multiple linear regression analysis.Ã‚Â The results show that age and nationality have significant effect, while gender has insignificant effect on financial performance. However, simultaneously all of the independent variables significantly affect the Return on Asset, with the coefficient determinant in this research is 20.8%.